2022
DOI: 10.1101/2022.04.28.489891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The “LINC” in between Δ40p53-miRNA axis in the regulation of cellular homeostasis

Abstract: Recently, we showed that Δ40p53, the translational isoform of p53, can inhibit cell growth independently of p53 by regulating microRNAs. Here, we explored the role of Δ40p53 in regulating the lncRNA-miRNA axis. Based on early research from our laboratory, we selected LINC00176 for further exploration. LINC00176 levels were affected by the overexpression and knockdown of Δ40p53. Further, under DNA damage, ER stress, and glucose deprivation, LINC00176 was upregulated in HCT116 p53-/- cells (harboring only Δ40p53… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
(166 reference statements)
0
2
0
Order By: Relevance
“…We found that Δ40p53 (and not FLp53) uniquely regulates miR-186-5p, which can downregulate expression of the known oncogene Ying Yang 1 (YY1) protein, thereby decreasing cell proliferation 22 . In another study we have also found that Δ40p53 regulates lncRNA (LINC00176) which can control cell fate mediated through multiple miRNA and mRNAs 23 . Contrary to its tumor suppressive role Δ40p53 independently activates the netrin-1 promoter and promotes cell survival 24 .…”
Section: Introductionmentioning
confidence: 81%
“…We found that Δ40p53 (and not FLp53) uniquely regulates miR-186-5p, which can downregulate expression of the known oncogene Ying Yang 1 (YY1) protein, thereby decreasing cell proliferation 22 . In another study we have also found that Δ40p53 regulates lncRNA (LINC00176) which can control cell fate mediated through multiple miRNA and mRNAs 23 . Contrary to its tumor suppressive role Δ40p53 independently activates the netrin-1 promoter and promotes cell survival 24 .…”
Section: Introductionmentioning
confidence: 81%
“…It has been shown that the p53 isoforms contribute to the regulation of the p53 pathway by regulating the expression of p53 target genes 9,10,11 . Notably, p53 isoforms exhibit both overlapping and distinct functions compared to the canonical p53 11,12,13 and have been reported to promote tumor progression in various cancers 11,14 . The p53 isoforms are generated through alternative promoter usage, alternative splicing, and alternative transcription starting site usage 9,15 .…”
Section: Introductionmentioning
confidence: 99%